Memperlengkai Pelayan Tuhan di Era Digital: Mengajarkan Ilmu Administrasi dalam Upaya Mendigitalisi Pelayanan Gerejawi - Safatulus Giawa (TEMISIEN: Jurnal Teologi, Misi, dan Entrepreneurship, 2023)
The church has faced challenge after challenge throughout the ages. One thing to remember is that the church was able to overcome these challenges and still exists today. Since the COVID-19 pandemic hit the world, new challenges have emerged for the church. The church ministry was shocked and forced to change the face of its ministry through virtual media. This era is known as the digital age. This new challenge becomes a problem for the church how to use media and technology to provide faith-building services to congregation members who are in an active condition using social media. For this reason, it is deemed necessary to formulate an administrative approach in an effort to digitize ecclesiastical services. In this study, the relationship between the church and theological colleges was found as a Christian institution that simultaneously thought about and designed the building of the faith of the congregation. This research uses literature review and descriptive method. From the theory found, an analysis was carried out to obtain administrative contributions for the church in digitizing ecclesiastical services. The finding in this study is that the church must open up to changes in service patterns and involve themselves in the theological college network. To face the challenges that exist, the church can apply administrative science to design and equip God's servants to face the demands of ministry in the digital era. This research concludes that efforts to digitize services are a must, considering that congregation members spend more time on social media, starting from Sunday school children to adults. That is why the church must pay serious attention to how the pattern of ecclesiastical services is digitized to reach and mature the faith of the congregation.